Modelling of dental geometry configuration / Mohd Shafiq Azni - Azni, Mohd Shafiq (2018)
In dentistry, determining the position and orientation for each tooth is mostly based on orthodontic qualitative perception. There is no standard method to obtain those values especially in three dimensional (3D) image which gives difficulty in some complicated cases. This study characterized and modeled a dental occlusal geometry structure, formulated methodology for dental position and orientation movement, and also demonstrated the concept of methodology. Based from images in CBCT scan software, 3D model of teeth was created using 3D modelling software to get a clearer view of teeth features. Every dental features are observed to find the best point in defining centroid for tooth. After defining the centroid, measurement tools in CBCT scan software were used to get the value needed directly from CBCT scan image. Using robot arm movement concept as reference, the methodology of position and orientation were formulated. Result from this study concluded that the centroid for one root teeth is defined as 1/3 of root to crown end. For teeth with two or more roots, the centroid is defined as the bifurcation point of tooth. Using that centroid, teeth position and orientation are obtained referred to reference frame which is the cone beam coordinate system in CBCT scan software. Transformation matrix was used to formulate the teeth orientation and position. From image processing software, data obtained were compared. There were some differences.